LOCAL POLITICAL PARTICIPATION OF THE ELDERLY ACCORDING TO THE PRINCIPLE OF BRAHMAVIHARN 4 IN SILA TOWN MUNICIPALITY MUENG KHON KAEN DISTRICT KHON KAEN PROVINCE - phalee, nattorn (Journal of Humanities and Social Sciences Mahamakut Buddhist University Isan Campus, 2024)
The objective of this thesis is as follows: 1) To study the level of community participation in local political affairs among the elderly according to Brahma Viharn 4. 2) To compare the level of community participation in local political affairs among the elderly according to Brahma Viharn 4, categorized by gender, age, educational level, and occupation. 3) To study suggestions for improving community participation in local political affairs among the elderly according to Brahma Viharn 4 in the municipality of Sila, Mueang Khon Kaen District, Khon Kaen Province, using a questionnaire to collect data from a sample group of 376 individuals. The statistical analysis used includes frequency, percentage, mean, and standard deviation, t-test, one-way ANOVA, and LSD. The research findings are as follows: 1) Overall, the public has a high level of opinion regarding community participation in local political affairs among the elderly according to Brahma Viharn 4 in the municipality of Sila, Mueang Khon Kaen District, Khon Kaen Province. 2) When comparing the opinions of the public on community participation in local political affairs among the elderly according to Brahma Viharn 4 in the municipality of Sila, Mueang Khon Kaen District, Khon Kaen Province, it was found that the opinions differ significantly among individuals of different genders, ages, educational levels, and occupations, with statistical significance at the 0.05 level. 3) Suggestions indicate that the elderly should actively participate in monitoring the performance of local governance to promote transparency. They should also be involved in policy -making for local development. Additionally, they should stay informed about local governance through online media and public forums. The public should be encouraged to participate in meetings with local government organizations to present issues and collaborate on finding solutions for further development.